2007
DOI: 10.2140/jomms.2007.2.439
|View full text |Cite
|
Sign up to set email alerts
|

A semi-infinite higher-order displacement discontinuity method and its application to the quasistatic analysis of radial cracks produced by blasting

Abstract: We introduce a higher-order indirect boundary element method in a traction-free half-plane known as semi-infinite displacement discontinuity method. The method is modified to use the linear elastic fracture mechanics principles for radial crack analysis in brittle materials like rocks. In this numerical method there is no need to discretize the traction-free boundary of the half-plane into higher-order elements thus decreasing the number of elements without affecting the accuracy of the solution to the desired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…If distribution of displacement discontinuity along the length of an element is not constant and changes in linear, quadratic or cubic form then it is called a higher order element which has been used to calculate displacement discontinuities along that element [18,19]. Figure 3 shows the displacement discontinuity along the elements and also the positive direction of displacements discontinuity for each element along the length of it.…”
Section: Higher Order Displacement Discontinuity Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If distribution of displacement discontinuity along the length of an element is not constant and changes in linear, quadratic or cubic form then it is called a higher order element which has been used to calculate displacement discontinuities along that element [18,19]. Figure 3 shows the displacement discontinuity along the elements and also the positive direction of displacements discontinuity for each element along the length of it.…”
Section: Higher Order Displacement Discontinuity Methodsmentioning
confidence: 99%
“…Results showed that discontinuum-based DEM has the potential in simulating rock indentation and fragmentation by TBM cutters when rock joints are taken into consideration [14]. The use of boundary element method for analysis and simulation of cracks can be traced in some studies [15][16][17][18][19][20][21]. Displacement discontinuity method is an indirect boundary element method which has been used for the analysis of crack problems.…”
Section: Introductionmentioning
confidence: 99%
“…The Riemann-Hilbert method can be adopted to solve 2D crack problems in an infinite, homogeneous, anisotropic plate [8]. A general higher-order DD method coupled with an indirect BEM has been applied to the quasi-static analyses of radial cracks produced by blasting [9]. Complex crack problems such as multiple branched and intersecting cracks also have been investigated using the numerical manifold method [10], which also has been applied to 2D http://dx.doi.org/10.1016/j.engfracmech.2014.…”
Section: Introductionmentioning
confidence: 99%
“…Although the constant displacement discontinuity elements are simple and widely used for analyzing engineering problems, they cannot predict the stresses and displacements for field points closer than approximately one element length from the boundary and also for the crack analysis a higher accuracy of the results near the crack tips is needed. Therefore, the higher order variation of the displacement discontinuities together with special crack tip elements are usually used for the treatment of crack problems (Scavia, 1995;Shou and Crouch, 1995;Tan et al, 1996;Marji et al, 2006;Fatehi Marji et al, 2007;Hosseini Nasab and Fatehi Marji, 2007;Fatehi Marji et al, 2009). Kinked cracks in brittle rocks under compressive loading are studied by Bobet (2000), Kishen and Sing (2001); Sagong and Bobet (2002), Wong et al (2001Wong et al ( , 2002 and Tang et al (2005).…”
Section: Introductionmentioning
confidence: 99%